Traffic Officers Attendance System Design Using GPS and IMEI Smartphone - Adnan Buyung Nasution (INFOKUM, 2021)
The reduction of traffic congestion level in the capital is not only viewed from the side of road width, vehicle density, and waiting time at the traffic signs but also no less important is the presence of traffic officers who secure every traffic crossroads. Therefore, it takes a system design that can perform online attendance at the traffic officer. This design utilizes a smartphone device that is IMEI (International Mobile Equipment Identity) as an identification officer and GPS (Global Positioning System) as a marker of attendance at the crossing of traffic signs. By using IMEI and GPS is expected to know the position and identity of officers and work time on the officer.